2022
DOI: 10.1111/inm.13071
|View full text |Cite
|
Sign up to set email alerts
|

Maternal predictors of children's mental health in low‐income families: A structural equation model

Abstract: Low-income populations are particularly susceptible to mental health problems, and the susceptibilities of family members may be interconnected. In particular, maternal factors are known to be linked to their children's outcomes. This study aims to investigate how maternal cognition, depression, and the mother-child relationship, as well as children's cognition, predict the mental health of children in low-income families. Pairs of mothers and children from families receiving governmental assistance were surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The first step in this hypothetical pathway is partially supported by previous studies from within the UK which have identified that the mediating role of maternal mental health problems is of particular importance in the context of economic disadvantage [14,15]. The second step is also supported by growing evidence from out-with the UK to suggest that at least some of the association between economic hardship and children's mental health outcomes may be mediated via the impact of poverty on the quality of parent-child relationships [16,17]. Specifically, several North American studies have found social welfare policies that increase household income without disrupting the amount of time parents are able to spend with their children can lead to significantly improved childhood mental health outcomes, through improving parent-child relationships [18,19].…”
Section: Introductionmentioning
confidence: 71%
“…The first step in this hypothetical pathway is partially supported by previous studies from within the UK which have identified that the mediating role of maternal mental health problems is of particular importance in the context of economic disadvantage [14,15]. The second step is also supported by growing evidence from out-with the UK to suggest that at least some of the association between economic hardship and children's mental health outcomes may be mediated via the impact of poverty on the quality of parent-child relationships [16,17]. Specifically, several North American studies have found social welfare policies that increase household income without disrupting the amount of time parents are able to spend with their children can lead to significantly improved childhood mental health outcomes, through improving parent-child relationships [18,19].…”
Section: Introductionmentioning
confidence: 71%